S plesom do zdravja - Premelč, Jerneja (Šport (Ljubljana), 2016)
Parkinson's disease is the second most common neurodegenerative disease, afflicting more than 7,000 patients in Slovenia. Dance therapy is very successful for Parkinson's patients and, in other countries, it is used as a tool to improve a number of abilities in patients diagnosed with parkinsonism and some other diseases. Dance therapy improves motor abilities and consequently walking, body posture and the movement of the hands and fingers. Moreover, it reduces depression and anxiety and improves cognitive abilities. Music motivates patients to exercise more intensively and longer and thus feel greater satisfaction. With all of its positive influences, dance therapy improves the quality of lives of Parkinson's patients.
Keywords: dance; dance therapy; health; parkinsonova bolezen; Parkinson's disease; ples; plesna terapija; sport; šport; zdravje